NF-κB/TWIST1 Mediates Migration and Phagocytosis of Macrophages in the Mice Model of Implant-Associated Staphylococcus aureus Osteomyelitis - Wang, Yutian; Lin, Yihuang; Cheng, Caiyu; Chen, Pengyu; Zhang, Ping; Wu, Hangtian; Li, Kaiqun; Deng, Ye; Qian, Jikun; Zhang, Xianrong; Yu, Bin (Frontiers in Microbiology, 2020)
Staphylococcus aureus (S. aureus) infection-induced osteomyelitis is a great challenge in clinic treatment. Identification of the essential genes and biological processes that are specifically changed in mononuclear cells at an early stage of S. aureus osteomyelitis is of great clinical significance. Based on transcriptional dataset GSE16129 available publicly, a bioinformatic analysis was performed to identify the differentially expressed genes of osteomyelitis caused by S. aureus infection. ERBB2, TWIST1 and NANOG were screened out as the most valuable osteomyelitis-related genes (OMRGs). A mice model of implant-associated S. aureus osteomyelitis was used to verify the above genes. We found significantly up-regulated expression of TWIST1 in macrophages and accumulation of macrophages around the infected implant. Meanwhile, S. aureus infection increased the expression of TWIST1, MMP9 and MMP13, and stimulated the migration and phagocytosis function of Raw 264.7 cells. Additionally, knock-down of the expression of TWIST1 by siRNA could significantly down-regulate MMP9 and MMP13 and suppress the migration and phagocytosis ability of macrophages in response to S. aureus infection. Furthermore, we found that NF-κB signaling was activated in Raw 264.7 cells by S. aureus and that inhibition of NF-κB signaling by Bay11-7082 blocked the expression of TWIST1, MMP9 and MMP13 as well as cell migration and phagocytosis evoked by S. aureus. Our findings demonstrate that NF-κB/TWIST1 is necessary for migration and phagocytosis of macrophages in response to S. aureus infection. Our study highlights the essential role of NF-κB/TWIST1 in early innate immune response to S. aureus infection in bone.